Gas phase complexes of H3N⋯CuF and H3N⋯CuI studied by rotational spectroscopy and ab initio calculations: the effect of X (X = F, Cl, Br, I) in OC⋯CuX and H3N⋯CuX. Issue 19 (3rd May 2016) - Bittner, Dror M.; Stephens, Susanna L.; Zaleski, Daniel P.; Tew, David P.; Walker, Nicholas R.; Legon, Anthony C.
Abstract : Complexes of H3 N⋯CuF and H3 N⋯CuI have been synthesised in the gas phase and characterized by microwave spectroscopy. Abstract : Complexes of H3 N⋯CuF and H3 N⋯CuI have been synthesised in the gas phase and characterized by microwave spectroscopy. The rotational spectra of 4 isotopologues of H3 N⋯CuF and 5 isotopologues of H3 N⋯CuI have been measured in the 6.5–18.5 GHz frequency range using a chirped-pulse Fourier transform microwave spectrometer. Each complex is generated from a gas sample containing NH3 and a halogen-containing precursor diluted in Ar. Copper is introduced by laser ablation of a solid target prior to supersonic expansion of the sample into the vacuum chamber of the microwave spectrometer. The spectrum of each complex is characteristic of a symmetric rotor and a C 3v geometry in which the N, Cu and X atoms (where X is F or I) lie on the C a 3 axis. The rotational constant ( B 0 ), centrifugal distortion constants ( D J and D JK ), nuclear spin-rotation ( C bb (Cu) = C cc (Cu)) constant (for H3 N⋯CuF only) and nuclear quadrupole coupling constants ( χ aa (X) where (X = N, Cu, I)) are fitted to the observed transition frequencies. Structural parameters are determined from the measured rotational constants and also calculated ab initio at the CCSD(T)(F12*)/AVQZ level of theory. Force constants describing the interaction between ammonia and each metal halide are determined from D J for each complex. Trends in the interaction strengths and geometries of B⋯CuX (B = NH3, CO) (X = F, Cl, Br, I) are discussed.